Family Communication Patterns, Self-Esteem, and Depressive Symptoms: The Mediating Role of Direct Personalization of Conflict. (4th May 2017) - Curran, Timothy; Allen, Jordan
Abstract : This study examined personalizing conflict as a mediator in the relationship between family communication patterns and psychological health factors. Data were collected from 249 participants, who completed measures of conversation orientation, conformity orientation, direct personalization of conflict, depressive symptoms, and self-esteem. Results showed significant indirect effects from conformity orientations to both depressive symptoms and self-esteem through direct personalization of conflict. Also, results showed a significant indirect effect from conversation orientation to depressive symptoms through direct personalization of conflict. These findings suggest that personalizing conflict interactions is one way in which family communication patterns and psychological health are linked.